Miss Blanche en de Van Moppes-diamanten : een moralisties manifest - Van Duijn, Roel (Roeland Hugo Gerrit), 1943-; Stoop, Olaf; Wessing, Koen (Amsterdam : Unit, 1967)
Roel van Duijn, one of the spearheads of the Dutch countercultural Provo movement, wrote this manifesto in 1967, six months after Provo had been carried to its grave. The contents of this handsome little book are still very much in the vein of Provo: subversive, provocative, creative, and humorous. In a playful manner and packaged as an adventure story Van Duijn (here spelled as Van Duyn) reflects on labour, exploitation, individual and social virtues, creativity, and life and death. Miss Blanche (a popular cigarette brand in those days) is staged as Van Duijn's mysterious and sexy mentor and partner in crime. (Miss Blanche had been launched as Van Duyn's fictitious counterpart two years earlier in Provo pamphlet #15.) Van Duyn and Miss Blanche decide to steal the diamonds of Amsterdam diamond-seller Van Moppes and return them to their rightful owners: the black mineworkers of South-Africa. During the adventure they get locked in the diamond-seller's vault, which leaves them plenty of time to reflect on all sorts of matters, until Van Moppes's son arrives. The capitalist exploiter is promptly seduced by Miss Blanche and knocked unconscious by Van Duyn. Provo draughtsman and underground publisher Olaf Stoop designed the front cover of this edition. The back cover shows a photo by Koen Wessing